2023
DOI: 10.3390/plants12040729
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Non-Structural Carbohydrates Release in Chinese Fir Topsoil and Canopy Litter at Different Altitudes

Abstract: Non-structural carbohydrates (NSCs) are labile components in forest litter that can be released quickly at the early stage of litter decomposition and accelerate the metabolic turnover of soil microorganisms, which is essential for the formation of forest soil organic matter. Therefore, understanding the NSCs response mechanisms to forest litter at different altitudes is critical for understanding nutrient cycling in the forest soil under climate change conditions. In this study, we used the net bag decomposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…We took the Chinese fir litter back to the laboratory, separated the twigs and leaves, and air-dried them. In this study, twigs and leaves were placed into nylon decomposition bags with a size of 20 × 20 cm and a mesh size of 0.5 mm, and each bag weighed 10 g ± 0.005 air-dried (2.5 and 7.5 g of twigs and leaves, respectively) [23]. Five bags of the prepared samples were used to determine the initial nutrients.…”
Section: Experimental Designmentioning
confidence: 99%
“…We took the Chinese fir litter back to the laboratory, separated the twigs and leaves, and air-dried them. In this study, twigs and leaves were placed into nylon decomposition bags with a size of 20 × 20 cm and a mesh size of 0.5 mm, and each bag weighed 10 g ± 0.005 air-dried (2.5 and 7.5 g of twigs and leaves, respectively) [23]. Five bags of the prepared samples were used to determine the initial nutrients.…”
Section: Experimental Designmentioning
confidence: 99%
“…It is indigenous to China, Vietnam (northern regions) and partially found in Laos and Cambodia. This species holds great significance as a timber resource in South China, playing a vital role in the country's forestry development and ecological stability [20]. Notably, Chinese fir exhibits robust growth characteristics and offers excellent raw materials.…”
Section: Introductionmentioning
confidence: 99%
“…A strong factor is also anthropogenic loading on the forest ecosystems (Hedwall et al, 2019). Classic forest-science studies and modern specialists (Chevaux et al, 2022;Zlobin et al, 2022) identified that the main types of such effects of plants of one stratum on plants of another stratum are: a) effects of upper-stratum plants on the lower ones through light reduction, increased root competition for water and nutrients in the soil, formation of a specifically structured forest litter, and formation of a certain allelopathic biochemical environment (Schönbeck et al, 2021;Wu et al, 2023); b) influence of lower-stratum plants on the upper-stratum plants through reduction of potential niches of recovery of tree species and control of development of their undergrowth.…”
Section: Introductionmentioning
confidence: 99%